2014
DOI: 10.3109/14767058.2013.879705
|View full text |Cite
|
Sign up to set email alerts
|

Labor length among overweight and obese women undergoing induction of labor

Abstract: Objective Maternal weight is thought to impact labor. With rising rates of obesity and inductions, we sought to evaluate labor times among induced women by body mass index (BMI) category. Methods Retrospective cohort study of term inductions from 2005 to 2010. BMI categories were: normal weight (NW), overweight (OW), and obese (Ob) (18.5–24.9, 25–29.9, ≥30kg/m2). Kruskal-Wallis tests compared median latent labor (LL) length and active labor (AL) length. Chi-square determined associations. Multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
2
13
2
Order By: Relevance
“…However, the survival curves that illustrated the duration of active labor were not visually different between normal weight, overweight and obesity classes I and II, in contrast to the survival curves from latent labor when the duration successively increased with BMI class. This finding is in contrast to the previous mentioned study that analyzed latent labor, in which no association was identified with maternal BMI; however, different definitions of the labor phases were employed (71). Our results on latent labor must be considered in light of the factors that may have biased the results.…”
Section: Induced Laborcontrasting
confidence: 98%
See 2 more Smart Citations
“…However, the survival curves that illustrated the duration of active labor were not visually different between normal weight, overweight and obesity classes I and II, in contrast to the survival curves from latent labor when the duration successively increased with BMI class. This finding is in contrast to the previous mentioned study that analyzed latent labor, in which no association was identified with maternal BMI; however, different definitions of the labor phases were employed (71). Our results on latent labor must be considered in light of the factors that may have biased the results.…”
Section: Induced Laborcontrasting
confidence: 98%
“…It has been demonstrated that the duration of the total time in induced labor increases with a higher maternal weight at the time of delivery (45,59,67,68) and failure to progress is a more common indication for cesarean delivery in obese women with IOL than normal weight women (69,70). Limited studies have assessed the effect of maternal early pregnancy BMI on the duration of induced labor, with contradictory results (58,64,71).…”
Section: Induction Of Labor In Obese Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Students T-Tests were used to compare continuous data between the two independent groups and chi-square tests were used to compare categorical data after testing for normality using Kolmogorov-Smirnov tests. Parity was used as a covariate (nulliparous versus multiparous) in analyzing total time in labor and time in stage 2 of labor as parity has a significant effect on these variables in previous studies 21 , as well as in our dataset (nulliparous women spent significantly more time in stage 2 than multiparous women regardless of physical activity levels, p<0.001). We also stratified our groups by parity in order to better understand the impact of physical activity on time in labor in exclusively nulliparous versus multiparous obese women.…”
Section: Discussionmentioning
confidence: 98%
“…Parity was used as a covariate (nulliparous versus multiparous) in analyzing total time in labor and time in stage 2 of labor as parity has a significant effect on these variables in previous studies 21 , as well as in our dataset (nulliparous women spent significantly more time in stage 2 than multiparous women regardless of physical activity levels, p<0.001). We also stratified our groups by parity in order to better understand the impact of physical activity on time in labor in exclusively nulliparous versus multiparous obese women.…”
Section: Methodsmentioning
confidence: 98%